Measuring the Impact of Financial Performance Indicators on Credit Employment Rates in Traditional Private Banks Operating in Syria - قبرصلي, صبا; رولا غازي اسماعيل; رامي كاسر لايقة (Latakia University Journal - Economic and Legal Sciences Series, 2024)
The aim of this research is to measure the impact of financial performance indicators (turnover ratio, equity to assets ratio, equity to total deposits ratio, total income to total assets ratio, market value to book value ratio, net profit to total income ratio, return on assets ratio, return on equity ratio, net interest and commission to total assets ratio) on credit employment rates in traditional private banks operating in Syria. The descriptive-analytical approach was adopted, and the data of all private commercial banks operating in Syria, from 2011 to 2020, were analyzed. The research found a set of results, the most important of which are: A statistically significant negative effect of return on equity, market-to-book value ratio, and net profit to total income ratio on the employment rate. A statistically significant positive effect of the ratio of net interest and commissions to total income on the employment rate. There is no statistically significant effect of each of the following on the employment rate: (trading ratio, debt ratio, equity ratio, equity to total deposits, total income to total assets, return on assets).